O criador e a criatura: movimentos escriturais na construção das personagens do romance Dona Anja, de Josué Guimarães - Andretta, Luana Maria (2019)
This research, based on the studies of genesis and character, deals with the creative process developed by the gaucho writer Josué Guimarães in the characters’ construction of the novel Dona Anja, published in 1978. Therefore, the objective that guides our analyzes is to investigate the movements in the characters’ construction in the cited novel, in a selected dossier, as a broadening or new meaning’s possibility about social-historical profiles and functions of the female figure, and political-ideological, the male figure, and as a means of raising assumptions about the form of character composition of that author. We use a prototext sketch on the characters’ physical and psychological characteristics in the book, as well as the first published edition, both documents are from the collection of the Acervo Literário Josué Guimarães (ALJOG/UPF). Thus, our study establishes a comparative movement between the two elements of the dossier to identify scriptural movements - understood as variants, differences from one version of the text to another. Having a qualitative approach bias, the research, regarding the technical procedures, is bibliographic, when making the theory survey in books and articles in the area, and documentary, when dealing with a material not systematized before. In this way, in the first theoretical chapter, whose main compasses on genetic criticism are Hay (2007), Pino and Zular (2009) and Biasi (2010), the essential genetic notions for dealing with manuscripts and work in a literary collection are explored, the specific lexicon of this science, its analysis’ object and the instances in which the writer and geneticist are situated. In the second theoretical chapter, based mainly on the contributions to character of Rosenfeld and Candido (1976), Brait (2017) and Reis (2018), we draw a brief diachronic view of the character and deal with the composition resources of the fictional entity with a contemporary look. The analysis’ chapter brings in more detail the methodological procedures, the life and work of the author analyzed, the Acervo Literário Josué Guimarães, brief notes on the Brazilian civil-military dictatorship and a summary of the novel explored. Moreover, it is in this chapter that we find the investigation of scriptural movements in the composition of the Josué Guimarães’ characters, which we will call josuesiana in Portuguese. Finally, in the final considerations, we can conclude that the scriptural movements identified in Dona Anja’s female characters resume the analysis, indicating that the female characters have socio-historical functions belonging to a conservative and patriarchal society, in which their role is serve men as sexual objects, without political role or speech force. The biographical erasure evidenced in these characters points to a typified narrative that not only relates to the social functions outside the work, but also maintains a close connection with the internal coherence of the novel. With male characters, discontinuities are less severe, but the type characters remain. Josué understands that his characters, in Dona Anja, are verbal masses and, therefore, manipulates them according to the narrative’s composition, but, in a personal writing gesture, conceives them, in the prototext, a breath of life: the brief biographies.